Financial Inclusion and Urban Marginality: A Review of Barriers Faced by Those Below The Poverty ‎Line Households in Delhi’s Slums - Tokas, Ms. Nikita; Gupta, Dr. Devkanya (International Journal of Accounting and Economics Studies, 2025)
Financial inclusion has emerged as a critical driver of poverty alleviation and sustainable ‎development, yet urban marginalized populations in India continue to face significant barriers. ‎This study examines the socio-economic, institutional, technological, and cultural factors influencing financial inclusion among Below Poverty Line (BPL) households in Delhi’s slums. Adopting a ‎mixed-methods approach, the research combines a household survey of 150 respondents with 20 ‎in-depth interviews. The survey data were analyzed using descriptive statistics, chi-square tests, ‎and qualitative thematic analysis. Reliability and validity were ensured through pre-testing of ‎survey instruments, triangulation of data sources, and consistency checks. The findings reveal a ‎persistent gap between account ownership (63.3%) and active usage (40%), highlighting that ‎access alone does not ensure inclusion. Education emerged as a significant predictor of account ownership, with primary and higher education being strongly associated with greater financial inclusion (χ² = 32.54, p < 0.001). Institutional barriers such as stringent Know Your Customer (KYC) ‎norms, lack of formal identity documentation, and limited banking infrastructure within slums ‎further constrained access. Technological barriers, particularly digital illiteracy and poor ‎connectivity, reinforced exclusion despite growing emphasis on digital banking. Qualitative data ‎underscored issues of distrust in financial institutions, fear of debt, and gendered social norms ‎restricting women’s participation. Policy recommendations include simplified and flexible KYC ‎norms, targeted financial literacy programs, expansion of banking and digital infrastructure in ‎slums, and community-driven initiatives such as strengthening Self-Help Groups (SHGs). ‎Importantly, the study links these interventions to broader economic outcomes, such as reducing ‎reliance on informal credit and enhancing household resilience, thereby strengthening its ‎relevance for policymakers and financial institutions. Theoretically, the study refines the Capability ‎Approach by showing that access to financial services does not automatically expand financial ‎capabilities without literacy, trust, and institutional support. It also extends Institutional Theory, ‎demonstrating how bureaucratic rigidity and weak institutional trust perpetuate exclusion. ‎Together, these contributions advance the understanding of financial inclusion in contexts of urban ‎marginality and provide actionable insights for inclusive urban development‎.